2021
DOI: 10.1038/s41523-021-00224-w
|View full text |Cite
|
Sign up to set email alerts
|

Clinical behavior and outcomes of breast cancer in young women with germline BRCA pathogenic variants

Abstract: Young breast cancer (BC) patients carrying a germline BRCA pathogenic variant (mBRCA) have similar outcomes as non-carriers. However, the impact of the type of gene (BRCA1 vs. BRCA2) and hormone receptor status (positive [HR+] vs. negative [HR−]) on clinical behavior and outcomes of mBRCA BC remains largely unknown. This is an international, multicenter, hospital-based, retrospective cohort study that included mBRCA patients diagnosed, between January 2000 and December 2012, with stage I–III invasive early BC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 43 publications
2
28
0
Order By: Relevance
“…Over the past years, with an increasing prevalence of breast cancer worldwide ( 1 4 , 6 ), the comprehensive and individualized management for patients with this particular disease has gradually attracted much attention, especially in terms of young breast cancer ( 7 , 9 , 10 , 14 , 15 ). It was believed that age was an independent prognostic indicator among female breast cancer and younger age, especially under the age of 40 years, frequently presented a higher risk of locoregional metastasis, recurrence, and ultimately worse OS outcomes ( 7 , 10 , 12 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past years, with an increasing prevalence of breast cancer worldwide ( 1 4 , 6 ), the comprehensive and individualized management for patients with this particular disease has gradually attracted much attention, especially in terms of young breast cancer ( 7 , 9 , 10 , 14 , 15 ). It was believed that age was an independent prognostic indicator among female breast cancer and younger age, especially under the age of 40 years, frequently presented a higher risk of locoregional metastasis, recurrence, and ultimately worse OS outcomes ( 7 , 10 , 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…First, although the sample size of this study was considerable, the character of the retrospective design was inevitably flawed with bias. Second, some clinical risk factors like Ki-67 index ( 36 , 37 ) and BRCA1- and BRCA2- related mutation ( 15 , 38 ) as well as high 21-Gene Recurrence Score (21-GRS) ( 39 ) which have been proved to be related to worse OS in patients with breast cancer were unavailable in the SEER database. Third, the detailed information of hormone receptors (estrogen receptor and progesterone receptor) and Her-2 status were unavailable in the SEER database.…”
Section: Discussionmentioning
confidence: 99%
“…The apparent negative impact in breast cancer of g BRCA1 or g BRCA2 pathogenic variant carriers could not be demonstrated, even in young women. In this context, no statistically significant differences in OS were observed between BRCA -positive and BRCA -negative patients in the multicenter prospective POSH study, which genotyped 2,733 young women (< 40 years) with invasive breast cancer and included a total of 338 (12%) patients with g BRCA m. 37 In addition, analyzing a retrospective cohort of 1,236 patients with stage I-III invasive early breast cancer at age ≤ 40 years, Lambertini et al 16 importantly showed that irrespective of hormone receptor status, the type of BRCA gene did not have a prognostic impact on OS between patients harboring BRCA1 - and BRCA2 -mutated tumors.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Although the predictive value of germline BRCA pathogenic variants (g BRCA m) in breast cancer has been demonstrated for PARP inhibitor agents, the prognostic value of these mutations in the HR+ subgroup remains controversial. 11-16 In addition, estrogen receptor (ER)–positive breast cancers are more common in CHEK2 and ATM pathogenic variant carriers and the prognostic value of these alterations is being elucidated. 17-20…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation